A simple model of the diffusion phenomena taking place during the debittering process of green table olives - Maldonado, Mariela; Zuritz, Carlos A.; Wuilloud, Rodolfo G.; Bageta, Carlos R.; Terreni, Jorge; Sanchez, María José (Instituto de la Grasa, CSIC (España), 2022)
The change in the concentration of sodium and calcium ions in the olive flesh and in the lye during the debittering process was quantified. The average concentration of Na increased from 0.0045 to 0,395 meq Na/g of olive flesh and the concentration of Ca increased from 0.018 to 0.0252 meq Ca/g of olive flesh. The firmness of the olives decreased almost linearly from 375 gf to 235 gf during the alkali treatment. The olives also suffered a 25.9% loss in their initial content of reducing sugars. A hypothetical simplified description of the dynamic of ionic charge changes and unwinding of the pectinic structure during the debittering process of green olives has been proposed. In addition, the effective diffusion coefficients were calculated for sodium and calcium using a diffusion model for a composite flat plate and constant diffusion coefficients. The coefficients for both solutes were in the order of 10–12 m2/s for the skin and 10–10 m2/s for the flesh. In both cases, the diffusion coefficients of Na were larger than the diffusion coefficients of Ca.